ANALISIS PENGARUH LIKUIDITAS, AKTIVITAS, PROFITABILITAS DAN GROWTH TERHADAP RETURN SAHAM (Pada Perusahaan Mnufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2017) - Mei Linda Dwi Wahyuni, 15.05.52.0290; Susilowati,, Yeye (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of liquidity (CR), activity (TATO), profitability (EPS) and growth on the stock return of manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period.The sampling method used was purposive sampling, with 106 data processed. The analytical tool used is multiple regression analysis. The test hypothesis used t-statistics and f-statistics at a significant level of 5%.The results of this study indicate that profitability (EPS) has a significant positive effect on the stock return, while liquidity (CR), activity (TATO) and growth do not affect the stock return.